Streamlining WELL concepts of office buildings for developing countries: The case of Malaysia - Tan, Carmen Y. M.; Abdul Rahimi, Abdul Rahman; Xia, Bo; Chen, Qing (American Society of Civil Engineers (ASCE), 2022)
The research aims to identify WELL concepts that support office building occupants’ health, well-being, and productivity in a developing country. Individual semi-structured interviews were conducted to collect data from occupants working in office buildings. Thematic analysis was used to analyze the collected data. In addition to the existing ten concepts in WELL Building Standards, three new WELL concepts have been identified: “Security and Safety,” “Building Services and Maintenance,” and “IT Infrastructure” are significant in supporting occupants’ wellness for office buildings in developing countries. Compared to developed countries, security and safety are highly concern due to the high-crime rates. Additionally, poor building services and maintenance and low support IT Infrastructure are lacking in sustaining the occupants’ wellness. Hence, this research revealed office building occupants’ needs in a developing country through the WELL concepts. These findings can assist government bodies of developing countries in streamlining WELL rating tools.